Electromyostimulation and plyometric training effects on jumping and sprint time - Herrero, J. A.; Izquierdo, M.; Maffiuletti, N. A.; Garcia-Lopez, J. (International Journal of Sports Medicine, 2006)
This study compared the effects of four-week training periods of electromyostimulation (EMS), plyometric training (P), or combined EMS and P training of the knee extensor muscles on 20 m sprint time (ST), jumping ability (Squat jump [SJ] and Countermovement jump [CMJ]), maximal isometric strength (MVC), and muscle cross-sectional area (CSA). Forty subjects were randomly assigned to one of the four treatment groups: electromyostimulation (EG), plyometric (PG), combined EMG, and P (EPG), that took place 4 times per week, and a control group (CG). Subjects were tested before and after the training program, as well as once more after 2 wk of detraining. A significant improvement (p < 0.05) in ST was observed after training (2.4 %) in EG while a significant slowing (p < 0.05) was observed (- 2.3 %) in EPG. Significant increases in EPG (p < 0.05) were observed in SJ (7.5 %) and CMJ (7.3 %) after training, while no significant changes in both jumps were observed after training and detraining for EG. A significant increase (p < 0.05) in MVC was observed after training (9.1 %) and after detraining (8.1 %) in EG. A significant increase (p < 0.05) in MVC was observed after training (16.3 %) in EPG. A significant increase (p < 0.01) in CSA was observed after training in EG (9.0 %) and in EPG (7.1 %). EMS combined with plyometric training increased the jumping height and sprint run in physically active men. In addition, EMS alone or EMS combined with plyometric training leads to increase maximal strength and to some hypertrophy of trained muscles. However, EMS training alone did not result in any improvement in jumping explosive strength development or even interfered in sprint run.